2014
DOI: 10.1590/1415-52732014000400001
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity and socioeconomic, food and nutrition profile of schoolchildren living in urban and rural areas of Picos, Piauí

Abstract: ObjectiveThis study aimed to determine the prevalence of food insecurity among schoolchildren living in urban and rural areas of Picos, Piauí associated with the socioeconomic profile of families and their food intake and nutritional status. MethodsStudy participants were families with children aged 7-10 years enrolled in municipal schools, totaling 342 families/schoolchildren. The study was conducted at school facilities through interviews with mothers -or guardians -using a questionnaire based on the Brazili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1
15

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 22 publications
2
4
1
15
Order By: Relevance
“…Some studies have already identified a relation between food insecurity and overweight, since it has increased in the economically disadvantaged classes, probably due to the acquisition of foods with low nutritional value and high caloric density at lower prices 9,25,26 . In contrast to other studies 9,[27][28][29][30] , schooling showed no association with FNI, probably because this population is very homogeneous regarding low schooling, a result also found in other settled populations 7,21,31 . Low schooling contributes to people generally not getting well paid work opportunities outside the settlements, not promoting increased income and decreased food insecurity.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Some studies have already identified a relation between food insecurity and overweight, since it has increased in the economically disadvantaged classes, probably due to the acquisition of foods with low nutritional value and high caloric density at lower prices 9,25,26 . In contrast to other studies 9,[27][28][29][30] , schooling showed no association with FNI, probably because this population is very homogeneous regarding low schooling, a result also found in other settled populations 7,21,31 . Low schooling contributes to people generally not getting well paid work opportunities outside the settlements, not promoting increased income and decreased food insecurity.…”
Section: Discussioncontrasting
confidence: 99%
“…It is known that low family income is one of the main determinants of FNI. 9,[27][28][29][30]32,33 In this population, the average monthly income was R$ 651.00 (US$192,69) , a figure slightly lower than the minimum wage in force in 2013, which was R$ 678.00 (US$ 200,59). Some 83.2% of the families received some type of government CTP.…”
Section: Discussionmentioning
confidence: 99%
“…Dentre os estudos (n = 12) predominou (n = 11) a aplicação da EBIA como método de avaliação da IA na população, utilizada sempre em conjunto a outros métodos de avaliação indireta [15][16][17][18][19][20][21][22][23][24][25] . Questionário socioeconômico e demográfico foi o método de avaliação indireto mais utilizado, estando presente em 66,6% (n = 8) dos trabalhos 4,15,[17][18][19][21][22][23] , sendo encontrada associação com a IA em todos estes.…”
Section: Resultsunclassified
“…Dentre os estudos (n = 12) predominou (n = 11) a aplicação da EBIA como método de avaliação da IA na população, utilizada sempre em conjunto a outros métodos de avaliação indireta [15][16][17][18][19][20][21][22][23][24][25] . Questionário socioeconômico e demográfico foi o método de avaliação indireto mais utilizado, estando presente em 66,6% (n = 8) dos trabalhos 4,15,[17][18][19][21][22][23] , sendo encontrada associação com a IA em todos estes. Observou-se associação entre IA e menor renda 15,17,20,23 ; produção insuficiente de alimentos 4,15 ; escolaridade 17 ; endividamento 15 ; número de moradores no domicílio maior que cinco 17 ; ausência de água tratada 19 ; local de moradia 4,18,22 ; e tipo de moradia 4 .…”
Section: Resultsunclassified
“…A study conducted in 2011 showed that 62% of beneficiaries of the Family Grant Program are in a situation of food insecurity and nutritional insecurity in the territory studied, showed that the excess weight, both overweight and obesity, a problem is more comprehensive than the low molecular weight, being 3.38% of the population studied were in malnutrition, 31% overweight and 21% with obesity 12 .…”
Section: Resultsmentioning
confidence: 99%